How does leader humility affect micro and small enterprises' organizational agility and marketing performance? - Indriati, Petiana (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study investigates how leader humility enhances organizational agility by creating a learning climate in micro and small enterprises (MSEs). Using data from 219 MSEs in Jakarta, we test a mediation model to understand better how humble leadership influences organizational adaptability. The results confirm that leader humility significantly strengthens the learning climate (supporting hypothesis H1) and improves organizational agility (H2). The results established a positive relationship between learning climate and agility (H3), partially mediating the relationship between humility and agility (H4), accounting for 30% of the overall effect. This study makes three key contributions: (1) it demonstrates the dual impact of humility on agility through both direct and mediated pathways in MSE contexts; (2) it validates the learning climate as an important, though partial, mediator; and (3) it reveals how informal learning dynamics in MSEs enhance these effects. Moreover, this research expands the leadership literature by empirically testing an integrated humility-learning-agility framework in Indonesia's often-overlooked MSE sector, where flexible leadership is vital for survival.